Religion, colonialism and gender : a postcolonial feminist study of selected works of North African and Asian Muslim women writers - Ishaque, Nausheen (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2017)
This research probes into the lives and experiences of Muslim female characters as depicted in the selected fiction of Muslim women writers from North Africa and Asia. The author chooses to work on four Muslim women writers from diverse global locations: Nawal El Saadawi from Egypt, Fatima Mernissi from Morocco, Qaisra Shahraz of Pakistani origin, and Adibah Amin from Malaysia. A common political (colonial) history and a shared religion (Islam) act as threads of connection among these places which are otherwise separated by geographical divisions, historical circumstances, languages and cultural practices. The study aims to interpret the selected texts functioning in the context of both patriarchal and colonial oppressions and systems of knowledge construction. It is carried out especially to examine the rights and space granted to Muslim women in their respective socio-religious settings. It looks at the way the hermeneutics of Islam deal with issues like marriage and divorce, domestic violence, female celibacy, veiling, polygamy, literacy and social activism among women, widowhood, prostitution, female genital mutilation and many more in the postcolonial ethos. In addition, it highlights the foregrounding of Islam by the selected authors in their texts with an end to see if they adhere to the Orientalist beliefs or subscribe to their own religio-cultural legacy. With its focus on the female body and religion, the study also analyses the role religious traditions play in perpetuating – or challenging – female body politics and the violence attached to it. The study deploys postcolonial feminism as a theoretical approach for conducting textual analysis of the fictional works selected for this study. The results of the study show that violence and malpractices (against women) are frequently legitimized and perpetuated in the name of Islam. Nonetheless, such practices are either the products of biased male scholarship (in religion) or the traditional/tribal androcentricity and have practically nothing to do with the normative teachings of Islam.